2002
DOI: 10.1172/jci0214340
|View full text |Cite
|
Sign up to set email alerts
|

Thyrostimulin, a heterodimer of two new human glycoprotein hormone subunits, activates the thyroid-stimulating hormone receptor

Abstract: IntroductionHuman thyrotropin (TSH), follitropin (FSH), lutropin (LH), and chorionic gonadotropin (CG) are members of the glycoprotein hormone family derived from heterodimerization of a common α subunit with hormone-specific β subunits. These hormones were originally purified from the anterior pituitary (TSH, LH, and FSH) and placenta (human CG) and shown to activate specific G protein-coupled receptors in the thyroid (TSH receptor) and gonads (LH and FSH receptors), respectively (1-4). These three pituitary-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…The absent increased 131 I uptake also excludes the presence in these patients of a bioactive TSH-like substance (Nakabayashi et al, 2002) which by stimulation of the thyroidal production of T 4 and T 3 suppresses native TSH.…”
Section: Discussionmentioning
confidence: 83%
“…The absent increased 131 I uptake also excludes the presence in these patients of a bioactive TSH-like substance (Nakabayashi et al, 2002) which by stimulation of the thyroidal production of T 4 and T 3 suppresses native TSH.…”
Section: Discussionmentioning
confidence: 83%
“…This study revealed that flr‐2 encodes a homolog of GPA2, the alpha subunit of thyrostimulin, a glycoprotein hormone discovered most recently (Nakabayashi et al. 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Thyrostimulin, a newly discovered glycoprotein hormone consisting of two glycoprotein subunit‐related genes, α2 (GPA2) and β5 (GPB5), activates the thyrotrophin (TSH) receptor (TSHR) both in vitro and in vivo (1). Because GPA2 and GPB5 co‐localise in the rat and human anterior pituitary where the TSHR is known to be expressed, a paracrine role for thyrostimulin was suggested (1–3). However, the putative biological role for the heterodimer in vivo is still a matter of debate (4–6).…”
mentioning
confidence: 99%